Career Consulting: Formation and Development in Ukraine - Stoliaruk Khrystyna S. (Bìznes Inform, 2020)
The article is concerned with researching the prospects for development of services in the sphere of career consulting in Ukraine. The relevance and importance of improving the career competence, in particular with the help of relevant specialists in the public and private sectors of career consulting, has been proven. Thus, during their professional life people face a variety of career problems: career crises, time outs, dissatisfaction with work, professional burnout, etc. On the one hand, this results from imperfection of the system of career orientation, therefore, the suboptimal choice of profession. On the other hand, the dynamism of the modern labor market, caused by economic changes, active processes of automation, robotics and digitalization, forces people to reconsider their professional scenario. This necessitates the development of consulting services in career management. That is why the object of research is the processes of formation and development of the career consulting market in Ukraine. The article presents the results of the research on the readiness of Ukrainians to consult a specialist for career advice; the analysis of the foreign experience of the organization and practice of career consulting, together with the possibilities of applying it in Ukraine, is carried out. This allowed to allocate the key directions of the public and private sectors of these services: on the part of the State (except for the assistance of career advisers in employment centers) - the involvement of education sphere in the issue of ensuring the career competence of young people; on the part of the private sector - help to the people who do not intend to apply to public employment centers for various reasons, but want to get the opportunity to consult an independent expert for career advice. The article also analyzes the prospects for certification of these specialists and the relevance of developing professional standards for providing services in the sphere of career consulting. Foreign approaches to defining the quality of work of career consultants and, in particular, the activities of providers of these services are presented. Thus, the author realizes the goal set - deepening the theoretical and methodological knowledge in the organization of both the public and the private sectors of the national career consulting market.